ANALISIS KEMAMPUAN BERIPIKIR KREATIF MATEMATIS SISWA SMP - Tomi Suparman; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study discusses the problem of students in solving creative mathematical problems and renewal where students do the problem also to learn the level of ability to think mathematically creatively. The method used in this research is descriptive qualitative research. While the population in this study were all junior high school students in the city of Bandung, while the sample was 30 grade VIII students in one of the junior high schools in the city of Bandung. The results obtained from this study indicate that indicators of flexible thinking and original indicators of thinking in students' creative thinking abilities obtain the lowest percentage of 41.67% and 39.06% respectively. Then the mistakes made by students in solving mathematical creative thinking problems are given in several aspects of making mathematical processes, regulating the adequacy of not and the concepts that are contained, and wrong in calculating operations. The level of students' creative thinking skills are still relatively low, as seen from the number of mistakes students make in completing test questions mathematical creative thinking skills.